2016
DOI: 10.1016/j.celrep.2016.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic Analysis of the UV-Induced DNA Damage Response

Abstract: SummaryIn order to facilitate the identification of factors and pathways in the cellular response to UV-induced DNA damage, several descriptive proteomic screens and a functional genomics screen were performed in parallel. Numerous factors could be identified with high confidence when the screen results were superimposed and interpreted together, incorporating biological knowledge. A searchable database, bioLOGIC, which provides access to relevant information about a protein or process of interest, was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
176
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(196 citation statements)
references
References 51 publications
18
176
0
2
Order By: Relevance
“…Gene expression profiling by 4sU-Seq also revealed that changes in newly synthesized RNA upon IR exposure are extensive, indicating that the transcriptional response is global not only upon UV irradiation (Boeing et al 2016) but also upon DSB formation. Nevertheless, to establish effective DDR, a timely expression of subset of transcripts that code for DNA repair, signaling, cell cycle, and cell survival factors, is necessary.…”
Section: Ddx54 In Genotoxic Stress Responsementioning
confidence: 99%
“…Gene expression profiling by 4sU-Seq also revealed that changes in newly synthesized RNA upon IR exposure are extensive, indicating that the transcriptional response is global not only upon UV irradiation (Boeing et al 2016) but also upon DSB formation. Nevertheless, to establish effective DDR, a timely expression of subset of transcripts that code for DNA repair, signaling, cell cycle, and cell survival factors, is necessary.…”
Section: Ddx54 In Genotoxic Stress Responsementioning
confidence: 99%
“…3). Interestingly, a growing number of studies have reported data to suggest that (i) UV irradiation preferentially inhibits elongation, rather than transcription initiation [28][29][30]38 , (ii) P-TEFb and NELF are important regulators of UVresponse 41,54,69 and (iii) although elongation gradually decelerates due to the encounter of Pol II with DNA lesions, significant initiation/early elongation activity (assessed by nRNA-seq) is observed in the first thousand bases of actively transcribed regions 28,29,38 , a characteristic that has also been used for the identification of active TSSs genome-wide after UV 30 . These features are consistent with our finding that new Pol II-hypo molecules are constantly recruited to PICs post-UV (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only six proteins were found to be ubiquitylated exclusively in ring stages, of which three are rhoptry proteins. Our bioinformatics analysis below is extrapolated from these qualitative label free experiments since our efforts to apply quantitative mass spectrometry approaches based on isotope labelling such as TMT or dimethyl labelling [27] were not compatible with the relatively low yield of modified peptides.…”
Section: The P Falciparum Ubiquitome: Distribution Of Ubiquitylationmentioning
confidence: 99%